AN EMPIRICAL ANALYSIS OF COCOA BEAN PRODUCTION IN GHANA - Darkwah, Samuel Antwi; Verter, Nahanga (European Scientific Journal, ESJ, 2014)
This article analyses cocoa production in Ghana from 1990 to 2011, using Johansen cointegration and OLS regression approaches. The results of the cointegration test show a long run equilibrium relationship between cocoa bean production, area harvested, the world price, cocoa export and RGDPK, all the variables were statistically significant. More so, the results from the OLS linear regression show a positive relationship between annual cocoa output and area harvested as well as export and RGDPK in Ghana. However, on the contrary, the results show a negative relationship between cocoa bean production and the world price. Arguably, this partly because the Ghanaian government has fixed the price of cocoa in order to protect farmers/growers from the shocks on the world market. However, this measure to some extend appears to be counterproductive, especially when the price cocoa beans increase in the world market without increase in the producer price. As a result, farmers are likely to respond to price signals in the opposite directions. The government of Ghana should create an enabling environment and some incentives by increasing cocoa farm gate prices relative to the prices on the world market, subsidizing farm inputs, and providing affordable loans to smallholder cocoa farmers to ensure sustainable cocoa bean production in the country.